The Context of Indonesian local culture in human resource and educational development: A systematic literature review - Hasyim, Muhammad Ardi Nupi; Dirgantari, Puspo Dewi (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Competitive advantage in today’s global era is largely determined by how human resources (HR) are managed and developed, including within the field of education. Rapid changes in global society have created interactions across countries in the economic, social, technological, and educational sectors, thereby increasing cross-cultural interdependence. However, research on the role of Indonesian local culture in HR and educational development remains relatively limited. In fact, the failure of many HR management and development practices is often linked to incompatibility with local cultural values. This article presents a systematic literature review to understand the development of research on the influence of local culture in Indonesia on HR and educational development. The systematic literature review method is applied to examine and synthesize previous studies in a structured manner. The findings indicate that integrating local culture into HR and educational development strategies enhances effectiveness, sustainability, and contextual relevance. Moreover, this study highlights the importance of adapting HR and educational management practices to local wisdom and values to address global challenges while strengthening national identity. This review is expected to provide contributions for academics, practitioners, and policymakers in designing more contextual, inclusive, and sustainable HR and educational development strategies.